Sales and survival within the contested acoustic territories of Mexico City's Historic Centre. Issue 3 (2nd September 2017) - Rasmussen, Anthony W.
ABSTRACT: The diverse and highly stylised cries ( pregones ) of street vendors are ubiquitous features of Mexico City's soundscape and audible manifestations of its cultural heritage. Throughout its history, Mexico City's Historic Centre has served as a site of informal commerce. However, the adoption of neoliberal economic policies and the privatisation of public spaces have produced a paradox. While the number of street vendors rises as options for gainful employment dwindle, the criminalisation of their means of subsistence has exposed these individuals to police bribes, confiscation and harassment. Sounds (e.g., street cries, whistles and coded language) are essential to the maintenance of this tenuous way of life. Sounds are used to lure customers, claim territory and execute highly coordinated evasions of police raids. This article explores the specialised listening and sound-making of street vendors and demonstrates the integral relationship between aurality and subaltern resistance in contemporary Mexico City.